2015
DOI: 10.1007/s11067-015-9290-x
|View full text |Cite
|
Sign up to set email alerts
|

The Classical Braess Paradox Problem Revisited: A Generalized Inverse Method on Non-Unique Path Flow Cases

Abstract: The classical Braess paradox problem refers to a user-equilibrium assignment model which all started with Braess's (Unternehmensforschung 12; 258-268, 1968) demonstrated example network. Some variants of Braess paradox and related theories were subsequently developed to detect this paradoxical phenomenon on a general network. In this paper, the authors are devoted to the classical Braess paradox problem involving situations whenever considering new links to be added to a network. Historical literature told us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Note that in the literature when investigating BP on road traffic networks, researchers have utilised linear cost functions [42][43][44], polynomial cost functions [45] and general monotonous non-decreasing cost functions [46]. We regress the cost function using linear function, polynomial function and cubic function and the results show that they have similar performance.…”
Section: Cost-function Formulationmentioning
confidence: 95%
“…Note that in the literature when investigating BP on road traffic networks, researchers have utilised linear cost functions [42][43][44], polynomial cost functions [45] and general monotonous non-decreasing cost functions [46]. We regress the cost function using linear function, polynomial function and cubic function and the results show that they have similar performance.…”
Section: Cost-function Formulationmentioning
confidence: 95%
“…The authors of [31,32] examined the necessary and sufficient conditions when the Braess paradox occurs for general networks with linear link-cost functions. Reference [33] proved that there is at least one O/D pair connected by a new path so that the Braess paradox does not (does) occur, as the proposed test matrix is positive (negative) and semi-definite. Reference [34] showed that the Braess paradox only occurs when the total travel demand falls within a certain intermediate range of demands.…”
Section: Braess Paradoxmentioning
confidence: 99%
“…This phenomenon is then analytically formulated by Mogridge et al (1987) and is named the "The Downs-Thomson Paradox (D-T Paradox)" thereafter. Furthermore, many other paradoxes have been studied in the transportation literature, including Braess paradox (Braess, 1968(Braess, , 2005Lin and Lo, 2009;Zhao et al, 2014;Di et al, 2014;Zverovich and Avineri, 2015;Hwang and Cho, 2015;, emission paradox (Nagurney, 2000), capacity paradox (Yang and Bell, 1998), stochastic assignment paradox (Sheffi and Daganzo, 1978;Yao and Chen, 2014), transit assignment paradox (Szeto and Jiang, 2014) and so on. This paper focuses on examining the D-T Paradox introduced by Downs (1962) and Thomson (1977).…”
Section: Introductionmentioning
confidence: 99%